Keeping Our Distance in Compassion-Based Social Relations - Smith, Steven (Journal of moral philosophy, 2005)
Abstract Although responding to ‘bad luck’ through instituting appropriate redistributive principles is a proper part of what justice entails, these principles must also paradoxically include the possibility of an agent-based response to misfortune that transforms adverse contingencies, such that the initial ‘bad luck’ becomes a positive part of the ‘sufferer's’ identity. This neo-Kantian accommodation within theories of justice signifies a ‘deep’ egalitarian empathic connectedness between persons, based on an equal respect for persons as agents (and not simply as passive victims of misfortune). Moreover, it is an accommodation that (a) can promote equality as ‘an end in itself’ rather than as merely a means to the end of enhancing a teleological conception of ‘well-being’ and ‘human flourishing’ and (b) can underpin a more robust Rawlsian conception of ‘justice as reciprocity’ than is usually allowed.